Penerapan peer dan self assessment sebagai tolok ukur penilaian kinerja siswa pada materi sistem koordinasi kelas XI SMA - Wulandari, Melyastuti; Sriyati, Siti; Purwianingsih, Widi (Department of Biology Education, Universitas Pendidikan Indonesia, 2020)
The implementation of peer and self assessment has become one of the alternative in doing the product of performance assessment. The research aims to describe student’s ability using peer dan self assessment as standard performance assessment on regulation system in senior high school students. Hopefully, the peer assessment can refer to the peer and self assessment. The research applied descriptive method which involved 25 student of the XI grade senior high school. The research instruments were research were the implementation research form, online form and rubric peer assessment, online self-assessment and student response questionnaire and teacher assessment. Peer assessment was implemented by students in groups and compared to teacher’s assessment. The result showed that the implementation of peer and self assessment was great. The student’s ability in doing peer and self assessment was great too, which means that peer and self assessment can be a standard of performance assessment. The comparation of the students’ assessment and teacher assessment show the similarity with percentage 84%. The type of feedback that many students gave was C1 type (Direction correction). Student respons of implementation peer and self assessment was great and they felt helpful by implementation of peer and self assessment.